Media Pembelajaran Alat Ukur Konsumsi Air Menggunakan Flow Sensor pada Matakuliah Sensor dan Aktuator: Media Pembelajaran Alat Ukur Konsumsi Air Menggunakan Flow Sensor pada Matakuliah Sensor dan Aktuator - Komang Aditya Pramana Putra; Wayan Mahardika Prasetya Wiratama; Agus Adiarta (Universitas Pendidikan Ganesha, 2026)
Conventional learning practices in the Sensor and Actuator course are often constrained by the limited availability of practical learning media that integrate current technologies. This study aimed to develop a water consumption measurement learning media using a flow sensor based on the Internet of Things (IoT) and solar energy through the ADDIE development model. The product consisted of a trainer, a user manual, and a tutorial video. The developed media was evaluated through expert validation and implementation involving undergraduate students of Electrical Engineering Education at Universitas Pendidikan Ganesha. The results indicated that the media achieved a feasibility score of 93% from both content and media experts. Furthermore, small-group and large-group trials obtained positive responses of 95.2% and 93%, respectively. These findings indicate that the developed learning media is highly feasible and can effectively support practical learning in the Sensor and Actuator course.